Competencies, milestones, and EPAs – Are those who ignore the past condemned to repeat it?. (1st September 2016) - Klamen, Debra L.; Williams, Reed G.; Roberts, Nicole; Cianciolo, Anna T.
Abstract: Background: The idea of competency-based education sounds great on paper. Who wouldn't argue for a standardized set of performance-based assessments to assure competency in graduating students and residents? Even so, conceptual concerns have already been raised about this new system and there is yet no evidence to refute their veracity. Aims: We argue that practical concerns deserve equal consideration, and present evidence strongly suggesting these concerns should be taken seriously. Method: Specifically, we share two historical examples that illustrate what happened in two disparate contexts (K-12 education and the Department of Defense [DOD]) when competency (or outcomes-based) assessment frameworks were implemented. We then examine how observation and assessment of clinical performance stands currently in medical schools and residencies, since these methodologies will be challenged to a greater degree by expansive lists of competencies and milestones. Results/Conclusions: We conclude with suggestions as to a way forward, because clearly the assessment of competency and the ability to guarantee that graduates are ready for medical careers is of utmost importance. Hopefully the headlong rush to competencies, milestones, and core entrustable professional activities can be tempered before even more time, effort, frustration and resources are invested in an endeavor which history suggests will collapse under its own weight.